An experimental study on vibration suppression of adjustable elliptical journal bearing-rotor system in various vibration states. (July 2020) - Zhang, Shenglun; Xing, Yu; Xu, Hua; Pei, Shiyuan; Zhang, Lei
Highlights: Adjustable Elliptical Journal Bearing (AEJB) is applied for vibration suppression of both rigid rotor and flexible rotor. Forced vibration of the rigid rotor can be suppressed obviously as the elliptical ratio increases. Resonance vibration of the flexible rotor can be reduced as the elliptical ratio decreases. Self-excited vibration of the flexible rotor can be eliminated by decreasing the elliptical ratio. Abstract: The working principle of an adjustable elliptical journal bearing was introduced in the previous work, and the physical model has been designed and manufactured. As a continuation of research work, the vibration suppression behavior of the bearing-rotor system in various vibration states are studied experimentally this paper. Two bearing-rotor test rigs are established based on the adjustable bearing. The rigid rotor test rig is built up to study the forced vibration suppression when the rotor is operated at a relatively large unbalance and far lower from the critical speed. The flexible rotor test rig is built up to study the suppression of resonance vibration and the elimination of self-excited vibration. The resonance vibration is tested during the flexible rotor passing through the critical speed. The oil whip self-excited vibration is tested when the flexible rotor is operated near twice of critical speed. Under heavier static load, the forced vibration amplitude of the rigid rotor is suppressed by 50% through increasing the elliptical ratio of the bearings. The suppression effect of forced vibration is up to 60% under lighter static load. During passing through the critical speed, the maximum resonance vibration amplitude of the flexible rotor is suppressed about 30% through decreasing the elliptical ratio of the bearing. When the flexible rotor is operated near twice of the critical speed, the oil whip self-excited vibration is weakened and eliminated eventually through decreasing the elliptical ratio of the bearing.